1997
DOI: 10.1097/00001756-199702100-00021
|View full text |Cite
|
Sign up to set email alerts
|

Allelic functional variation of serotonin transporter expression is a susceptibility factor for late onset Alzheimerʼs disease

Abstract: We examined a deletion/insertion promoter polymorphism of the serotonin transporter gene, which confers an approximately 40% reduction in expression of the protein, in 196 subjects with late onset Alzheimer's disease (AD) and 271 controls. The frequency of the 484 bp low activity allele was elevated in the subjects with AD (p = 0.004), and an excess of the low activity genotype (30%) was also found in comparison with the controls (20%) (chi 2 = 7.16; p = 0.03). This association was unrelated to the age of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
57
3
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 6 publications
11
57
3
2
Order By: Relevance
“…In summary, the present study supports the data of Li et al 24 and suggests that in addition to the ⑀4 apoE polymorphism, the low-activity 5-HTTLPR allele s is also a risk factor for AD, in accordance with the hypothesis of a multifactorial ethiology for the late onset form of this disorder. However, it is still unknown whether the association of 5-HTTLPR and AD is due to linkage desequilibrium or if this polymorphism acts directly on AD.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…In summary, the present study supports the data of Li et al 24 and suggests that in addition to the ⑀4 apoE polymorphism, the low-activity 5-HTTLPR allele s is also a risk factor for AD, in accordance with the hypothesis of a multifactorial ethiology for the late onset form of this disorder. However, it is still unknown whether the association of 5-HTTLPR and AD is due to linkage desequilibrium or if this polymorphism acts directly on AD.…”
supporting
confidence: 92%
“…23 However, no association between this polymorphism and bipolar disorders or schizophrenia was observed by us in Brazilian patients 21 or by other authors in schizophrenia, 22 panic disorder, 29 autism 23 and obsessive compulsive disorder. 30 For AD, results from the present study confirmed in a different population that the low activity allele of the serotonin transporter is a risk factor for AD, as recently reported by Li et al 24 Interestingly, however, the genotype distributions differed in the two studies which could be explained by the different genetic background of our population. In addition, we also observed that the genotype and gene frequencies for the 5-HTTLPR do not vary with age in normal subjects.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…[37][38][39] The larger reduction in GMVs in patients homozygous for the L-allele may then be explained by a larger susceptibility to neurodegenerative changes. However, this seems to be unlikely, although not exclusive, because our patients were young.…”
Section: Discussionmentioning
confidence: 99%
“…10 Associations have also been reported between the short allele of the 5-HTTLPR and severe alcohol dependence 11 and late-onset Alzheimer's disease. 12 A limitation of the negative studies is that their sample size is smaller than the original study of Lesch et al, 1 which leaves open the possibility of lack of statistical power. Here we report data from a population sample of 759 Caucasians which is larger than any study so far.…”
mentioning
confidence: 99%